Prevalence of chronic energy deficiency in the elderly population of Matlab - Rasheed, Sabrina; Khatun, Masuma; Hyder, S.M. Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
The number of elderly people in the world increased from 13 to 45 million between.1950 and 1985. In Bangladesh, however, the absolute number of elderly registered a slight decline. The negative growth rate reflects in part, poor health conditions and consequently high adult mortality rate. This study attempts to examine the nutritional status . of the elderly in ;Matlab, Bangladesh by looking at the prevalence of chronic energy deficiency (CED) among the elderly population and endeavors to find its determinant. Socioeconomic and nutritional information of 626 elderly individuals of 2076 households, residing in 14 villages of Matlab, Chandpur, was obtained through pre-coded questionnaires. The survey duration was April- August 1995. The results suggest that the eiderly are a vulnerable group of population in terms of health and nutrition, as 80% of the elderly population suffered from different degrees of CED and severe CED prevalence in elderly population was associated with sex, occupation, household economic status and family size.